Transverse momentum spectra and nuclear modification factors of charged particles in Xe–Xe collisions at sNN=5.44TeV - Acharya, S.; Torales-Acosta, F.T.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; et al. (Elsevier, 2019)
Transverse momentum (pT) spectra of charged particles at mid-pseudorapidity in Xe–Xe collisions at √sNN = 5.44 TeV measured with the ALICE apparatus at the Large Hadron Collider are reported. The kinematic range 0.15 < pT < 50 GeV/c and |η| < 0.8 is covered. Results are presented in nine classes of collision centrality in the 0–80% range. For comparison, a pp reference at the collision energy of √s = 5.44 TeV is obtained by interpolating between existing pp measurements at √s = 5.02 and 7 TeV. The nuclear modification factors in central Xe–Xe collisions and Pb–Pb collisions at a similar center-ofmass energy of √sNN = 5.02 TeV, and in addition at 2.76 TeV, at analogous ranges of charged particle multiplicity density dNch/dη show a remarkable similarity at pT > 10 GeV/c. The centrality dependence of the ratio of the average transverse momentum pT in Xe–Xe collisions over Pb–Pb collision at √s = 5.02 TeV is compared to hydrodynamical model calculations
Keywords: Charged-particle spectra; Xe–Xe collisions; Transverse momentum; https://purl.org/pe-repo/ocde/ford#1.03.04